THE USE OF ROBOTICS AND AUTOMATION IN IMPROVING PRODUCTIVITY IN THE ERA OF ECONOMY 5.0 - Caroline, Caroline; Loso Judijanto (CV. ADIBA AISHA AMIRA, 2025)
The use of robotics and automation in the era of Economy 5.0 has become a major catalyst in improving productivity in various industrial sectors. These technologies provide solutions to optimise operational efficiency by reducing time and costs, and consistently improving output quality. Despite the positive impact, this transformation also brings challenges in the form of changes to the labour market, which requires adaptation strategies through training and re-education. With a thoughtful and collaborative approach, the adoption of robotics and automation can lead to sustainable and inclusive economic growth, if balanced with policies that support social and economic sustainability.